Risk Communication Model in Facing Tsunami Disaster Through Stakeholder Engagement - Dian Agustine Nuriman; Puji Lestari; Marlinda Irwanti; Ridzki Sigit (Syntax Corporation Indonesia, 2022)
Umang Beach Club Private Island Resort is located in Sumur village, Pandeglang district, Banten. It has a very unique location, located at two sources of potential tsunamis. The first is Seismic, which is at the center of the megathrust of the Sunda Strait. The second, namely Unsesmic, is located at a distance of about 70km from Mount Anak Krakatu. This study aims to find a risk communication model in dealing with tsunami natural disasters through stakeholder engagement. This research uses descriptive qualitative method and data collection by interview, documentation and observation. Interviews were conducted with Umang Beach Club Private Island Resort, local government and disaster-related institutions, Sumur village communities, disaster communities as well as tsunami and risk management experts. The results of the study found a risk communication model in dealing with tsunami natural disasters through stakeholder engagement. Risk communication needs to be carried out in a systematic and planned manner and integrated with all stakeholders involved with disasters to reduce disaster risk.